PEDAGOGICAL CONTENT KNOWLEDGE: A CASE STUDY OF ESL TEACHERS - Moganashwari Kandasamy; Melor Md Yunus; Mohamed Amin Embi (TLEMC (Teaching and Learning English in Multicultural Contexts), 2018)
This is a case study on the pedagogical content knowledge of two ESL primary school teachers. The importance of pedagogical content knowledge among teachers is pertinent as the knowledge contributes significant influence on students’ performances and achievement. The research question addresses on 1) how pedagogical content knowledge (PCK) influences the ESL teachers’ instructional practice in classrooms 2) the challenges faced by ESL teachers in the teaching and learning process. The data was collected through observations and semi structured interview sessions for a period of five weeks. Atlas t.i. version 7 application was used to analyze the data. The findings revealed that the novice participant had sufficient pedagogical content knowledge but was not able to deliver the content successfully in a manner that the low achievers were able to comprehend. Alternatively, the experienced participant was confident in delivering the lesson using a variety of examples, teaching aids and also activities to ensure the lessons were successful. The major challenges both the novice and experienced ESL teachers faced were related to students’ attitude and motivation towards learning the subject. The study proposes the novice teachers to have a mentor to assist them for a good number of years. As for the experienced teachers they should keep themselves updated with the latest pedagogy, engage in good networking to exchange ideas and share insightful thoughts relevant to students’ achievement in mastering English exquisitely.